On the formation of pulses of coherent radiation in weakly inverted media - Kirichok, A.V.; Kuklin, V.M.; Mischin, A.V.; Pryjmak, A.V.; Zagorodny, A.G. (Вопросы атомной науки и техники, 2013)
A change in the character of maser generation in a two-level system is found when the initial population inversion exceeds some threshold value equal to the square root of the total number of atoms. Above this threshold, the number of photons begins to grow exponentially with time and the pulse with short leading edge and broadened trailing edge is generated. In this work, we attempt to explain the nature of this threshold. Coherent pulse duration, estimated by its half-width, increases significantly with increasing inversion, if all other parameters are fixed and the absorption is neglected. The inclusion of the energy loss of photons leads to the fact that the duration of coherent pulse is almost constant with increasing inversion, at least well away from the threshold. Виявлено зміну характеру процесу генерації випромінювання в дворівневій системі при перевищенні початкової інверсії заселеності величини, що дорівнює кореню квадратному з повного числа станів. При перевищенні цього порога число квантів починає рости з часом за експонентою. Зроблена спроба пояснити природу цього порога: при його перевищенні виникає генерація когерентного випромінювання у вигляді імпульсів з коротким переднім фронтом і протяжним заднім фронтом. Якщо всі параметри, окрім інверсії, зафіксувати, то з подальшим ростом інверсії при відсутності поглинання тривалість когерентного імпульсу, оцінена за його напівшириною, помітно збільшується. Урахування втрат енергії квантів призводить до того, що тривалість когерентного імпульсу практично не змінюється при зростанні інверсії, принаймні, досить далеко від порога. Обнаружено изменение характера процесса генерации излучения в двухуровневой системе при превышении начальной инверсии заселенностей величины, равной корню квадратному из полного числа состояний. При превышении этого порога число квантов начинает расти экспоненциально со временем. Сделана попытка пояснить природу этого порога: при его превышении возникает генерация когерентного излучения в виде импульсов с коротким передним фронтом и протяженным задним фронтом. Если все параметры, кроме инверсии, зафиксировать, то с ростом инверсии в отсутствие поглощения длительность когерентного импульса, оцененная по его полуширине, заметно увеличивается. Учет потерь энергии квантов приводит к тому, что длительность когерентного импульса практически не изменяется при росте инверсии, по крайней мере, достаточно далеко от порога.